2012
DOI: 10.1111/j.1748-5827.2012.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of prothrombin time and activated partial thromboplastin time in citrated whole blood samples from clinically ill dogs following storage

Abstract: Storage of citrated whole blood at room temperature for 24 or 48 hours did not significantly alter the measurement of prothrombin time but resulted in significantly shorter activated partial thromboplastin time results. Extrapolating from these findings, it is proposed that unseparated clinical samples that are submitted to an external diagnostic laboratory for the performance of clotting times, may generate reliable prothrombin time but unreliable activated partial thromboplastin time results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Most of these studies investigated patients on VKA, even though some evaluated that parameter in healthy individuals or in patients with hepatitis . It could be mentioned that such a stability of PT over time was also reported in samples collected from ill dogs that were evaluated after a delay of 24 or 48 hours …”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies investigated patients on VKA, even though some evaluated that parameter in healthy individuals or in patients with hepatitis . It could be mentioned that such a stability of PT over time was also reported in samples collected from ill dogs that were evaluated after a delay of 24 or 48 hours …”
Section: Discussionmentioning
confidence: 99%
“…The prothrombin time (PT) and activated partial thromboplastin time (aPTT) coagulation tests have been reported to be positively correlated with R values 36 . PT and aPTT have also been shown to be respectively prolonged and shortened over 24 hours of citrated whole blood storage at RT in dogs, but remained unchanged in blood stored at FT 37,38 . Some coagulation activation via the contact pathway is expected during sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…shown to be respectively prolonged and shortened over 24 hours of citrated whole blood storage at RT in dogs, but remained unchanged in blood stored at FT. 37,38 [41][42][43] Secondly, platelet metabolic activity drops due to a decrease in anaerobic glycolysis. 44 Thirdly, aggregation and clot strength have been shown to be enhanced by cold temperatures in multiple in vitro and in vivo studies, [45][46][47][48][49] 53 These two studies also did not compare results to baseline 30-minute values.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported previously in a study of 40 sick dogs that had coagulation panels performed, with the median PT being slightly below the RI and median aPTT within RI. 30 In a 2015 study of human patients undergoing elective surgery, PT and aPTT tests were found to be of low yield, given only 6–7%, respectively, were prolonged. 3 Our results suggest that CWA could complement SCT data, potentially contributing novel information to the laboratory evaluation of dogs with coagulation disorders.…”
Section: Discussionmentioning
confidence: 99%